Acute fatty liver of pregnancy simulating liver tumor. Issue 1 (28th November 2017) - Anon, Benjamin; Scotto, Béatrice; Bacq, Yannick
Key Clinical Message: Acute fatty liver of pregnancy (AFLP) is a rare liver disease unique to pregnancy that can lead to acute liver failure. Clinicians must have a high index of suspicion for AFLP because only early diagnosis and prompt delivery improve maternal and fetal prognosis. Abstract : Acute fatty liver of pregnancy (AFLP) is a rare liver disease unique to pregnancy that can lead to acute liver failure. Clinicians must have a high index of suspicion for AFLP because only early diagnosis and prompt delivery improve maternal and fetal prognosis.